Love actually (Universal, 2004)
It's all about love and holiday cheer in London. The Prime Minister is smitten with his caterer; a widower's young son nurses the ultimate schoolboy crush; a writer falls for his Portuguese housekeeper; a devoted wife and mother copes with her potentially unfaithful husband; and a lovelorn American is desperately attracted to a colleague.